Derivatives and its applications in foreign exchange risk management Vietnamese Import – export companies realities - Ngo, Xuan Truong (2011)
The purpose of the thesis is to give the main characteristics of derivatives and its strategies could be used to hedge against foreign exchange exposure. The audiences, after reading the paper, could have an overview of international trade and potential risks which entrepreneurs could meet when doing business in international environment. The thesis also provides readers solid knowledge about the foreign exchange rate, foreign exchange exposure, currency derivatives and strategies often used to hedge. The last part of the paper, I devoted to analyze the applying of derivatives to hedge against foreign exchange exposure in Vietnam import -- export oriented firms. Due to the less developed of infrastructure and technology as well as foreign exchange and capital markets, the derivatives which introduced around 10 years ago in Vietnam are not popular among Vietnamese firms. Other reasons contributed for the issue are lacking a clear corporate governance policy in firms and fixed exchange rate policy of Vietnamese government.